1970
DOI: 10.1063/1.3022044
|View full text |Cite
|
Sign up to set email alerts
|

Photoemissive Materials: Preparation, Properties, and Uses

Abstract: This is probably tho fint book on the subject after tho well known work by Hugh.. and DuBridge_ The author a well known worker in tbe field hu COllected in a single vDlume all relevant infomotion. on photoem".i .. materials which bave aD long been scattered in different Journa'._ Tho book i. mainly devoted to tho te Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 0 publications
2
41
1
Order By: Relevance
“…Also, it has been reported that the combination of K 2 CsSb grown on Si(100) was used as photocathode in a photoinjector 7 and the conductivity of the p-type Si-wafer simplifies the quantum efficiency measurement. Cathodes were grown following the recipe described by Sommer for the preparation of photomultiplier tubes (PMT), 8 where the sequence of evaporation starts with the antimony deposition onto the substrate, and subsequent alkali evaporations are performed sequentially, first potassium and then cesium. Antimony is evaporated from PtSb beads while the substrate is held at 100 • C and alkalis from Alvatec ® sources while the substrate temperature is held at 135 • C. The QE at 532 nm is monitored during alkali deposition, and once a plateau is reached, the evaporation is stopped.…”
mentioning
confidence: 99%
“…Also, it has been reported that the combination of K 2 CsSb grown on Si(100) was used as photocathode in a photoinjector 7 and the conductivity of the p-type Si-wafer simplifies the quantum efficiency measurement. Cathodes were grown following the recipe described by Sommer for the preparation of photomultiplier tubes (PMT), 8 where the sequence of evaporation starts with the antimony deposition onto the substrate, and subsequent alkali evaporations are performed sequentially, first potassium and then cesium. Antimony is evaporated from PtSb beads while the substrate is held at 100 • C and alkalis from Alvatec ® sources while the substrate temperature is held at 135 • C. The QE at 532 nm is monitored during alkali deposition, and once a plateau is reached, the evaporation is stopped.…”
mentioning
confidence: 99%
“…Research on photwathode materials has a venerable tradition, dating back to the optimization of photomultipliers earlier this century [Sommer, 1968;Cardona and Ley, 1978]. The operating characteristics of a laser driven electron gun are, however, very different from the requirements of photomultipliers, motivating a renewal search for photocathode materials.…”
Section: Generation Of Electron Pulsesmentioning
confidence: 99%
“…However, in order to accomplish an original and straightforward experiment, we chose Ag-O-Cs cathode material. Ag-O-Cs has the lowest work function among all the known thermal electron materials, about 0.8 eV, and is currently optimum in maximizing thermal electron emission at room temperature [6] . We adopted this material and let the tube and the whole closed circuit shown in In this experiment, the tube plays the role of an electric power source, and the load of the power source may be a resistor or a reversible battery.…”
Section: A Choice Of Thermal Electron Emitters and Working Temperaturementioning
confidence: 99%